Early feeding patterns among Mexican babies: findings from the 2012 National Health and Nutrition Survey and implications for health and obesity prevention. Issue 1 (December 2015) - Deming, Denise; Afeiche, Myriam; Reidy, Kathleen; Eldridge, Alison; Villalpando-Carrión, Salvador
Abstract Background Feeding practices and dietary factors associated with obesity in young children are now recognized to begin in infancy. Yet little is known about what specific foods and beverages Mexican children are consuming during the rapid dietary changes occurring in the first few years of life. The objective of this study was to describe the transitions in food consumption patterns of Mexican children from birth up to age 4 years and to assess their adherence to feeding guidelines that support growth, development and obesity prevention. Methods We analyzed cross-sectional, 24-hour dietary recall data from a nationally-representative sample of infants ages 0–11.9 months (m) (n  = 411), toddlers ages 12–23.9 m (n  = 538), and preschoolers ages 24–47.9 m (n  = 1108) from the Mexican National Health and Nutrition Survey 2012 (NHNS 2012). The prevalence of foods and beverages was estimated for specific age categories of children useful for examining detailed transitions in food consumption patterns and compared to international feeding guidelines for infants and young children. Results Few infants were exclusively breastfed (15 % ages 0–3.9 m; 4 % ages 4–5.9 m) and only ~1 % met the recommendation to exclusively breastfeed until at least age 6 m. One to 10 % of infants ages <6 m and 14–38 % of infants ages 6–11 m were fed cow's milk, a practice not recommended until after age 1 year. Most infants ages 0–3.9 m were meeting the recommendation to delay feeding of complementary foods until age 6 m, but by the age of 4–5.9 m, 9–37 % of infants were fed foods from nearly all of the major food groups. Few infants ages 6–11.9 m received iron-rich foods, (3–4 % iron-fortified infant cereals; 2–18 % meats). By the age of 9 m, more children consumed any type of sweet (75 %) than consumed a distinct portion of fruit (54 %) or vegetable (25 %). Sweetened beverages were fed with an increasing prevalence from 6 to 42 % in infancy, and reached 63 % by age 12 m and 78 % by age 24 m. Conclusions These data show that dietary patterns begin very early in life and many infants, toddlers and preschoolers in Mexico are not meeting important feeding recommendations aimed at supporting healthy growth, development and obesity prevention. These findings are useful to support the ongoing promotion of evidence-based feeding guidelines for young Mexican children.